Changing Caste Relations in Mudkhu Bhanjyang: An Anthropological Overview - Khatiwada, Thamindra (Patan Pragya, 2023)
This article attempts to analyze the changing caste relations in recent years in Mudkhu of Tarkeshwor Municipality of Kathmandu. Nepal has been declared a Federal Democratic Republic State; the political transformations have been made. Through a transformative process in Nepal, many existing social norms and patterns have been changed and some others have been reformed. With changing conditions of social structure and cultural practices, the Nepali caste system is also being changed. The rigidity of the caste system is changing. Due to various reasons and efforts flexibility is being taken place against caste-based discrimination in society. In recent decades, the structure and the functioning of the caste system and its economic and social aspects have greatly changed. There is an increase in class consciousness and a decrease in caste consciousness. It is, perhaps, because of the educational system, modernization, changing livelihood strategies etc.